Volumetric modulated arc therapy and concurrent chemotherapy for esophageal cancers: Dosimetric comparison with 3D conformal radiotherapy and early clinical results - Pawar, Y.S.; M.V., Manjula; Ramalingam, K.; R. S., Ashok (International Journal of Medical Research and Review, 2018)
Purpose: Despite Intensity Modulated Radiotherapy being the standard of care for most sites, 3D conformal radiotherapy (3DCRT) is still more widely used in esophageal cancers. This study compares dosimetric results of volumetric modulated arc therapy (RA) with that of 3DCRT and evaluates early clinical results of the patients treated with RA and chemotherapy. Materials and Methods: Evaluation of clinical outcomes in 10 patients treated definitively with RA and concurrent chemotherapy for esophageal cancer were included in the study. These patients were retrospectively planned with 3DCRT using antero-posterior portals till 3960cGy followed by obliques to a total dose of 5940cGy. The dose and target in each phase were kept same in both the plans. Dosimetric parameters were compared between the two plans using paired T-test or a Wilcoxon sign-rank based tests of normality on data distribution. Results: With a minimum follow-up of 4 months, all the patients tolerated the treatment without grade IV toxicities and treatment interruptions. 7 patients had a complete response and 3 had a partial response of which one patient underwent surgery and is disease free. RA resulted in higher conformity to the target compared to 3DCRT (mean conformity index 1.1 vs.1.8 respectively (p=0.002). RA plans significantly spared lung V15 (32%vs.40.2%, p=0.003), V20 (22.7%vs.29.7%, p=0.003), mean lung dose (13.8Gy vs.17.1Gy, p=0.003), heart V30 (46.8%vs.55.2% p=0.002), mean heart dose (24.3Gy vs.28.1Gy, p=0.003), and spinal cord maximum dose (44Gy vs.46.9Gy, p=0.002). The mean V5 and V10 values were similar with either technique. Conclusion: Irrespective of site of involvement, the RA resulted in better conformity and better sparing of heart, spinal cord and lungs beyond 15Gy. The dosimetric advantage gained with RA may become clinically relevant in reducing cardio-pulmonary complications especially in multimodality setting.